Organic matter decomposition in mountain peatlands: effects of substrate quality and peatland degradation - Charuni Jayasekara; Catherine Leigh; Jeff Shimeta; Ewen Silvester; Samantha Grover (Plant and Soil, 2025)
Background and Aims Peatlands occupy only 3% of Earth’s terrestrial lands but store about one-third of global soil carbon. However, these large carbon stocks are currently under threat due to peatland degradation, where altered hydrological balance could enhance peat oxidation; thus releasing large amounts of CO 2 into the atmosphere. We investigated the interactive effects of substrate quality, peat depth and peatland degradation on the decomposition rate of organic matter in peatlands by way of a field incubation experiment. Methods We incubated high-quality fresh peat and a lower-quality degraded peat substrate at three different depths (5, 15, and 30 cm) in two (intact and degraded) mountain peatlands for 18 months. Our results indicated that there is a significant interactive effect of substrate quality, peat depth, and peatland type on the peat decomposition rate. Results The fresh peat showed significantly higher decomposition rates than the degraded peat substrate, likely due to the high percentage of bioavailable carbon in the fresh moss substrate. In the degraded peatland, fresh peat at 30 cm showed no mass loss during the incubation period, likely due to the high-water table creating anaerobic conditions. The fresh peat incubated in the intact peatland showed a higher decomposition rate than the same substrate incubated in the degraded peatland due to the comparatively lower water table in the intact peatland. Conclusions Our findings indicate that the quality of the substrate being decomposed and the depth of the water table act as the main factors affecting the decomposition rate in mountain peatlands.